The efficiency of mutual fund families - Sanchez-Gonzalez, Carlos (Emerald Publishing Limited, 2018)
Sanchez-Gonzalez develops an innovative model that considers different management stages of mutual fund companies, overcoming the traditional dispute between the different approaches used in banking and insurance research. Research on the mutual fund industry has been primarily focused on mutual funds rather than on their management companies. This new work fills this gap in the empirical knowledge of the efficiency obtained by mutual fund management companies. The research analyses the Spanish case, which is one of the most relevant fund industries in the Euro market, providing new insights into issues that have not been explored prior. Data envelopment analysis (DEA) is the basic methodology used to evaluate the efficiency level. The book consists of two parts. The first part includes the basic concepts, a brief explanation of the basic DEA models, and a review of the most important applications to financial institutions. The authors formulate the multi-management stage model and the unique set of fund industry-specific variables used in this research. Subsequently, the efficiency of Spanish mutual fund companies is evaluated using the SBM approach. Finally, this part concludes and summarises the major findings of the efficiency analysis. The second part of the book reviews the major concepts of the variations in the original SBM approach and the more accurate empirical results of these SBM variants in the Spanish mutual fund industry. Subsequently, this part illustrates the persistence phenomenon to further determine whether any relevant factors may drive the efficiency results previously obtained. Finally, the second part presents conclusions and a summary of the major findings.